Effect of yarn type on moisture transfer characteristics of double-face knitted fabrics for active sportswear. (March 2020) - Sathish Babu, B; Senthil Kumar, P; Senthil Kumar, M
The properties of any clothing is decided by the constituent of its fibres, yarn and fabric structure. As clothing it should satisfy the wearer both in functional and aesthetic aspects. Thermal comfort is related to the temperature of the body and micro-environment between the fabric layer and the skin. The heat generated by the human body during strenuous activity must be dissipated to the external environment through the clothing. So the clothing worn next to skin should have the property of transferring the perspiration from the skin and to transfer the moisture to the atmosphere thus making the wearer to feel comfortable. Moisture transfer refers to the transfer of both moisture vapour and perspiration away from the body. The effect of yarn type on moisture transfer properties of double-face knitted fabrics has been studied with cotton, polypropylene, polyester, acrylic and nylon yarns. Four different double-face fabrics were produced using high-speed double circular knitting machine with inner layers as polypropylene, polyester, acrylic and nylon yarn and outer layer as cotton yarn. With respect to yarn type, 120 denier cotton and 120 denier polypropylene double-face knitted fabrics show better results for the moisture transfer characteristics as polypropylene has the ability to wick and transfer the moisture to the next layer of cotton in a faster way than the other three fabrics.